ANATOMICAL VARIATIONS OF TROCHLEAR SURFACE OF TALUS - Khadija Iqba (Journal of University Medical & Dental College, 2012)
ABSTRACT Objective: Anatomical variations of talar facets can be of help in pathologies of foot for reconstruction and rehabilitation procedures. So this study was designed to observe anatomical variations in tali. Study design: Observational analytical study. Settings and duration of study: The study was done at Islamic International Medical College, Rawalpindi and University Medical & Dental College, Faisalabad during Sept. 2010-March 2011. Methods: 300 adult tali were collected from different medical colleges of Rawalpindi, Islamabad and Faisalabad. Each talus was selected to mark the outline of the articulating surface carefully with the pencil. All the 300 tali were numbered and photographed. The articular facets were outlined with a black marker. The number of tali with a particular type of facets was noted and their percentages were calculated. The data was analyzed using SPSS version 17. The number and percentages were calculated for each type. Results: A. Medial extension of trochlear surface was present in 100 of the adult tali. B. Lateral extension of trochlear surface was present in 175 adult tali. C. Both Medial and Lateral extensions of trochlear surface was noticed in 25 adult tali. Conclusion: Both Medial and lateral extensions are less common as compared to lateral and medial extensions independently.